Analyzing the impact of tourism on Gross Regional Domestic Product (GRDP) in Central Java Province - Abdillah, Muhammad Ghulam Dzaki; Imaningsih, Niniek (PT. Riset Press International, 2024)
Indonesia is rich in natural resources, culture, and diversity in its social activities. This makes tourism a sector with potential as an economic booster. Central Java Province, in particular, is one of the provinces with a diverse and numerous array of tourist destinations. This diversity attracts both local and international tourists. Therefore, this research was conducted to determine the extent of the impact of the tourism sector on the Gross Regional Domestic Product (GRDP). The analysis method used is multiple linear regression with a 25-year time series data covering the number of tourist attractions, number of tourists, number of hotel accommodations, number of restaurants and eateries, and tourism sector investments as independent variables, and GRDP as the dependent variable. The results show that the number of tourist attractions and tourists has a positive and significant impact, while the number of hotel accommodations, restaurants, and eateries has a positive but not significant impact. Additionally, investment in the tourism sector has a negative and significant impact.